International Adoption Institute: Scientific and Legal Research and Analysis in the Light of Improving the Family Code of Russia - SHEVCHUK, Svetlana Stepanovna; MEL’NIKOVA, Marina Petrovna; KASHURIN, Ivan Nikolaevich; SAGALAEVA, Evgenia Sergeevna; PETROV, Nikolay Vladimirovich (Journal of Advanced Research in Law and Economics, 2018)
The article presents the research and analysis of the family and legal institute of adoption of Russian children by foreigners and stateless persons affecting the rights and interests of both Russian citizens and foreign nationals. The research covers the modern national legal base and the law enforcement practice in international adoption. The analysis involves the theoretical and practical problems of protecting the rights and interests of adopted children. The grounds are given for the necessity in developing and improving the international adoption legal regime. Based on the history of the international adoption institute and the comparative legal analysis of the same institutes in modern legal systems, the authors tried to define the key trends of the international adoption institute and to substantiate the most constructive proposals for its improvement.